Cyber Security: A Review of Cyber Crimes, Security Challenges and Measures to Control - Aastha Verma; Charu Shr
The proliferation of the Internet$1 (Bs interconnections has led to a substantial increase in cyberattack incidents, often with devastating and grave consequences for the organizations and their associated clientele. The pandemic of COVID-19 has pushed most organizations towards digital transformation. The higher dependence of a firm on digital infrastructure makes it more vulnerable to cyber-crimes. The existing literature suggests that the most notable and frequently chosen weapons of attackers are Internet of things (IoT) attacks, phishing attack, malware attack, distributed denial of service (DDoS) attack and structured query language (SQL) injection attack. In this study, an attempt has been made to generate a protection framework from these cyberattacks. In doing so, the present research has adopted a systematic stepwise process of investigation. The research method consists of four components. First, through bibliometric analysis in VOSviewer, authors identified the scope for searching the related literature published worldwide and generated visualization for comprehension. This step led to the selection of 60 research articles for further analysis. After that, each security threat$1 (Bs MAXQDA software word tree was developed, representing its linkages with possible security solutions and control measures. Lastly, they adopted expert elicitation protocol through semi-structured interviews with six corporate IT experts and five academic experts. The synthesis of information gathered leads to the development of a suggestive protection framework for the organizations.s